Assessment of air quality in home-school pathways.: Case of two primary schools in Jijel - Merabet, Zeyneb; Bouchair, Ammar (Journal of Architecture and environment of child, 2021)
In an urban environment, there are many sources of air pollution. The degree of exposure of individuals, and the capacity of urban fabrics to dilute pollutants depend on various parameters of shape and geometry. The effects on health are harmful, especially on children. This work aims to assess the air quality in the home-school pathways of two elementary schools in the city of Jijel, through the analysis of various urban parameters, and using the urban ventilation efficiency index (ACHvol). It turns out that several factors promote exposure to poor air quality on the way to the two schools. The recourse of urban ventilation efficiency clues and the new technologies in urban choices are promising tools to reduce the tragic effects on children's health in their daily pathways.